2019
DOI: 10.1002/lom3.10315
|View full text |Cite
|
Sign up to set email alerts
|

A novel freeze corer for characterization of methane bubbles and assessment of coring disturbances

Abstract: Aquatic ecosystems with organic‐rich sediments are a globally significant source of methane to the atmosphere. In shallow waters, ebullition is often a dominant emission pathway of methane. Current knowledge on the processes controlling gas bubble formation and persistence in aquatic sediments is limited. An important prerequisite for accurate quantification of the structure and methane bubbles in sediment samples is to preserve the ambient in situ conditions during the withdrawal process and further analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Due to the short time difference (approximately 36 h) between sampling and CT scan, the effect of increasing methane production can be assumed to affect θ , but to a minor extent. When comparing our results to those of Dück et al (), who showed that freezing of gassy clay sediments under laboratory conditions caused a contraction in θ by 27% ± 6%, it can be concluded that the greater differences in our study can be related to the changes in hydrostatic pressure and sample temperature, as described above.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Due to the short time difference (approximately 36 h) between sampling and CT scan, the effect of increasing methane production can be assumed to affect θ , but to a minor extent. When comparing our results to those of Dück et al (), who showed that freezing of gassy clay sediments under laboratory conditions caused a contraction in θ by 27% ± 6%, it can be concluded that the greater differences in our study can be related to the changes in hydrostatic pressure and sample temperature, as described above.…”
Section: Resultssupporting
confidence: 80%
“…This allows adjusting the core stratigraphy to remove the effect of shortening to their natural position to reduce the risk of an under‐ or overestimation of the core data. Dück et al () have shown that video imaging method for visualization of the freeze corer penetration into the sediment can bring a benefit in terms of quantification of shortening and is recommended to be used. In cases where the visibility at the benthic boundary layer is not good, the use of an echo‐sounding technique for the measurement of the penetration depth is recommended. Gravity coring is a relatively easy, cost‐efficient method and requires less effort than freeze coring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the drive mechanism of flap seals is relatively simple, only a torsion spring is needed. At present, the ice seal structure is widely used in natural gas sampling [46][47][48][49].…”
Section: Sealing Technologymentioning
confidence: 99%
“…Also, corers inevitably damage sediment during the sampling process, disrupting its structural integrity (e.g., see fig. 6 in Dück et al 2019). This significantly affects the free gas content and its quantitative estimates in cores.…”
mentioning
confidence: 99%